PERAN PEMBERDAYAAN EKONOMI KREATIF DALAM KESEJAHTERAAN MASYARAKAT TINJAUAN EKONOMI ISLAM - Habibulloh, Habibulloh (NATUJA: Jurnal Ekonomi Syariah, 2024)
Poverty is the main problem faced by the people of Papring Village, in the process of village and rural development. This is a reference for young people, agencies and the government, providing a strategic step in providing integrated services to the community, in order to eradicate the poverty rate that occurs in villages and rural areas. By providing empowerment to the community, to build an ideal economy. This research aims to analyze the role of creative economic empowerment in increasing income from an Islamic economic perspective, which occurs in Papring Village. This research uses descriptive qualitative research methods, using case study research and data collection by observation, interviews and documentation. The research results show that the creative economy plays an important role in improving people's welfare as evidenced by increasing sources of income, being able to channel aspirations/opinions, fostering a loyal attitude towards environmental changes, and the ability to make decisions. From an Islamic economic perspective, the creative economy plays a role in the piety of the people, the goodness of the government system, an attitude of caring, an attitude of justice and an attitude of equality.